Inferior vena cava syndrome caused by retroperitoneal fibrosis after pelvic irradiation: A case report - Naoya Murakami; Yasuaki Arai; Yoshiaki Takagawa; Kae Okuma; Kana Takahashi; Koji Inaba; Hiroshi Igaki; Yuko Nakayama; Jun Itami (Elsevier, 2019)
In this case report, we share our experience of a case with inferior vena cava (IVC) syndrome caused by secondary retroperitoneal fibrosis related to prior pelvic irradiation. A 60 year-old-female who has history of pelvic irradiation developed severe leg edema. Radiological examination revealed obstruction of IVC. Soon after recanalization of IVC with metallic stent placement, her symptom relieved. Keywords: Inferior vena cava syndrome, Metallic stent, Pelvic irradiation, Retroperitoneal fibrosis